Digital Measurement of the Construction Workers’ Performance through the Five-Minute Rating Method - Januardi, Redityo; Aliim, Muhammad Syaiful; Rochman, Saeful (PT Penjaminan Infrastruktur Indonesia (Persero), 2025)
The Five-Minute Rating method is a simplified approach used to measure workers’ performance based on time study principles, aimed to provide representative evaluations with minimal observation samples. However, its adoption in the construction industry remains low at only 6.4%, due to perceived impracticality and time-consuming implementation. A digital solution known as the Five-Minute Rating Solver (FMR-Solver), developed as an Android-based application, has been introduced. However, the practicality of its use and the efficiency of the measurement duration have yet to be studied. This study aims to measure the efficiency of the application tool in assessing worker effectiveness compared to using the conventional Five-Minute Rating method and to evaluate users’ perceptions of using the application. A case study was conducted during the installation of foundation reinforcement. The results show that the application tool can increase measurement efficiency by 22.6%. Evaluations by five users—based on criteria of stability, accuracy, understandability, operability, usefulness, and attractiveness—indicate validity scores ranging from 76.0% to 96.0%, falling within the categories of valid to very valid. The results suggest that the method offers a practical and effective alternative for construction workers’ performance and holds promise for wider industry adoption.